Effect Of Pretreatment By Sulfuric Acid On Cellulose Decomposition Using The In-Liquid Plasma Method - Kazuki, Tange; Shinfuku, Nomura; Shinobu, Mukasa; Hiromichi, Toyota; Syahrial, Fadhli (The Japan Institute of Energy Produced, 2016)
-